2011
DOI: 10.1016/j.ydbio.2011.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Altered differentiation and paracrine stimulation of mammary epithelial cell proliferation by conditionally activated Smoothened

Abstract: The Hedgehog (Hh) signaling network is critical for patterning and organogenesis in mammals, and has been implicated in a variety of cancers. Smoothened (Smo), the gene encoding the principal signal transducer, is overexpressed frequently in breast cancer, and constitutive activation in MMTV-SmoM2 transgenic mice caused alterations in mammary gland morphology, increased proliferation, and changes in stem/progenitor cell number. Both in transgenic mice and in clinical specimens, proliferative cells did not usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
51
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 34 publications
13
51
0
Order By: Relevance
“…This indicated that Smo activation leads to altered proliferation and differentiation. It was also reported that the frequency of regenerative stem cells in MMTV-SmoM2 mutant epithelia is decreased compared to the wild-type (Visbal et al, 2011). Here we demonstrated that a SmoM2;OCN-Cre mutant with constitutive Smo expression represses skeletal bone development and is involved in the retarded growth phenotype.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This indicated that Smo activation leads to altered proliferation and differentiation. It was also reported that the frequency of regenerative stem cells in MMTV-SmoM2 mutant epithelia is decreased compared to the wild-type (Visbal et al, 2011). Here we demonstrated that a SmoM2;OCN-Cre mutant with constitutive Smo expression represses skeletal bone development and is involved in the retarded growth phenotype.…”
Section: Discussionsupporting
confidence: 67%
“…Eventually, the Smo-mediated Gli activation leads to the expression of specific genes that promote cell proliferation and differentiation. Smo is also frequently and ectopically expressed in human breast cancers (Visbal et al, 2011), while altered hedgehog signaling is implicated in approximately 20-25% of all cancers (Briscoe and Therond, 2005). Considerable evidence has shown that sustained Smo-mediated activation of hedgehog signaling leads to increased proliferation and abnormal ductal morphology of the mammary gland, although Smo activation in luminal mammary epithelial cells was found only in a small percentage (-5%) of glands (Moraes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Recent work in a mouse model for breast cancer that induced ligand-independent Hh signaling by expression of a constitutively active smo allele demonstrated a non-cell autonomous effect on proliferation that may support tumor growth. 49 Furthermore, in samples from human breast cancer patients, cells with deregulated Hh activity did not label for the proliferation marker Ki67, implying a non-cell autonomous effect of deregulated Hh signaling. 50 Although these studies focused on proliferation, we demonstrate here that deregulated Hh signaling also increases resistance to apoptosis non-cell autonomously.…”
Section: Discussionmentioning
confidence: 97%
“…The mean SFE among biological replicate experiments varied from 0.06% to 1.55% for WT cells and from 0.015% to 0.85% for KO cells. Variability in the sphere assay among biological replicates by more than a log 10 factor is not unusual [196]. More importantly, SFE within each experiment was always greater for WT cells than for KO cells.…”
Section: Deletion Of Hif1a Decreases Tumorsphere Formationmentioning
confidence: 78%